Flash sintering of cationic conductive ceramics: A way to build multilayer systems. Issue 8 (7th April 2021) - Lachal, Marie; El Khal, Hana; Bouvard, Didier; Chaix, Jean‐Marc; Bouchet, Renaud; Steil, Marlu Cesar
Abstract: Flash Sintering (FS), that allows densifying ceramics at low furnace temperature in a few seconds, requires a reversible electrochemical reaction to enable the current flow through the electrode / material interface. For Li + pure ionic conductors such as Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP), the best material to ensure this fast charge transfer reaction is a mixed Li + /e − conductor, eg, LiCoO2 (LCO). This paper demonstrates the feasibility of FS on LCO between two Pt electrodes and on multi‐layers systems using LCO or LATP+LCO composite as electrodes. It is shown that a composite electrode both allows the flash event to occur and prevents the delamination possibly observed with pure LCO by lowering interfacial stresses. Abstract : Flash sintering of cationic ceramics: need for a reversible electrochemical reaction.